Synthesis, Characterization and Study Biological Activity of Some New Compounds Derived From Phthalic Anhydride - Nebras M. Jamel (Journal of Global Pharma Technology, 2018)
In this research ,  phthallic anhydride ring  is opened with 4-methyl aniline and acetone as a solvent  to results the compound [I] that reacted with dimethyl sulphate and anhydrous sodium carbonate formation to phathalate ester [II], while the acid hydrazide compound  [III], was obtained  from mixed the compound [II]with  hydrazine hydrate, Synthesis four type of shiff bases[IV]a-d   was synthesized  from the reaction  of acid hydrazide [III] with aromatic aldehyde or ketone , when reacted Shiff bases with   phthalic anhydride or naphthalicanhydride,I get eight derivatives  of oxazepine [V]a-d , [VI]a-d. The bacterial activity of the new compounds studied by four species of bacteria: Esherichia Coli, Enterobactecloacae (Gram negative) and staphylococcusaureus, Bacillus subtilis (Gram positive). These compounds were identified by FTIR,1HNMR and Mass (of some of them).Keywords: Schiff bass, 1, 3-oxazepine and antibacterial activity.